Transmission of SARS-CoV-2 and other infections at large sports gatherings: A surprising gap in our knowledge - Sassano, M.; McKee, M.; Ricciardi, W.; Boccia, S. (Frontiers in Medicine, 2020)
The first case of locally transmitted SARS-CoV-2 infection in Italy was recorded on February 18, 2020, in Codogno, in the region of Lombardy (1). Since then, the number of cases has increased rapidly, with 225,435 cases (or 0.37% of the population) by 17th May, 31,908 (14.15%) dying and 125,176 (55.53%) recovering (1). Lombardy is the epicenter of the disease in Italy. Accounting for 16.7% of the Italian population, it has had 37.64% of the country's cases, numbering 84,844 or 0.84% of the population (1). Within Lombardy, the province of Bergamo is among the hardest-hit in the country, with 12,443 COVID-19 cases, or 1.12% of the population. During March 2020, it saw an increase of 567.6% in daily deaths compared with the average in March 2015-2019 (Table 1) (1, 2). While the reason that Bergamo was so badly affected remains uncertain, several commentators, including the local mayor, have pointed to a football match.The first case of locally transmitted SARS-CoV-2 infection in Italy was recorded on February 18, 2020, in Codogno, in the region of Lombardy (1). Since then, the number of cases has increased rapidly, with 225,435 cases (or 0.37% of the population) by 17th May, 31,908 (14.15%) dying and 125,176 (55.53%) recovering (1). Lombardy is the epicenter of the disease in Italy. Accounting for 16.7% of the Italian population, it has had 37.64% of the country's cases, numbering 84,844 or 0.84% of the population (1). Within Lombardy, the province of Bergamo is among the hardest-hit in the country, with 12,443 COVID-19 cases, or 1.12% of the population. During March 2020, it saw an increase of 567.6% in daily deaths compared with the average in March 2015-2019 (Table 1) (1, 2). While the reason that Bergamo was so badly affected remains uncertain, several commentators, including the local mayor, have pointed to a football match.